2004
DOI: 10.1016/j.dsr.2004.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved organic carbon, nitrogen and phosphorus in the N-E Atlantic and the N-W Mediterranean with particular reference to non-refractory fractions and degradation

Abstract: Dissolved organic carbon (DOC), dissolved organic nitrogen (DON) and dissolved organic phosphorus (DOP) measured in deep profiles in the N-E Atlantic and in the N-W Mediterranean in the period 1984-2002 are described. After accurate validation, they show close agreement with those previously published. Classic profiles were obtained, with concentrations decreasing in deep waters. In the Mediterranean and in the Atlantic comparable concentrations were found in the 1500-2000 m waters, 44-46 μmol l −1 DOC, 2.6-2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 84 publications
(103 reference statements)
5
68
1
1
Order By: Relevance
“…Research has indicated that phytoplankton and zooplankton play a role in affecting DON and PON variations in the euphotic zone (Davis and Benner, 2005;Aminot and Kerouel, 2004;Bronk, 2002). Many studies have shown that phytoplankton and zooplankton biomass are affected by physical and biogeochemical conditions such as upwelling intensity, nutrient concentration and nutricline (Wang et al, 2005a(Wang et al, , 2006aLe Borgne et al, 1999, suggesting implications for the DON and PON variability.…”
Section: Relationships To Other Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has indicated that phytoplankton and zooplankton play a role in affecting DON and PON variations in the euphotic zone (Davis and Benner, 2005;Aminot and Kerouel, 2004;Bronk, 2002). Many studies have shown that phytoplankton and zooplankton biomass are affected by physical and biogeochemical conditions such as upwelling intensity, nutrient concentration and nutricline (Wang et al, 2005a(Wang et al, , 2006aLe Borgne et al, 1999, suggesting implications for the DON and PON variability.…”
Section: Relationships To Other Parametersmentioning
confidence: 99%
“…There have been reports of DON concentration in other parts of the ocean, showing a narrow range (4 to 7 mmol m −3 ) in a majority of the surface open ocean (Bronk, 2002;Aminot and Kerouel, 2004;Davis and Benner, 2005;Kahler and Koeve, 2001;Wong et al, 2002;Church et al, 2002). As Bronk (2002) summarized, the averaged DON concentration in the surface open ocean is 5.8 mmol m −3 with a standard deviation of 2 mmol m −3 .…”
Section: Model-data and Data-data Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…A steep pycnocline separates the ENACW from Mediterranean Outflow Water (MOW). The MOW extends down to about 1200 m, mixing with the underlying Labrador Sea Water marked by a salinity minimum at around 1800 m. There is some influence of Norwegian Sea Water at around 2000 m. Below this depth North Atlantic Deep Water (NADW) derived from Greenland appears, and is heavily influenced by the pervading Atlantic Antarctic Bottom Water at greater depths (Matthias and Godfrey, 2003;Aminot and Kerouel, 2004;De Mol et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Water masses in the North Eastern Atlantic have been described by Vangrieshem (1985) and Arhan et al (1994). Aminot and Kerouel (2004) summarised the water masses as North Atlantic Surface Water (max 100 m depth) overlying Eastern North Atlantic Central Water (ENACW) ( o700 m). A steep pycnocline separates the ENACW from Mediterranean Outflow Water (MOW).…”
Section: Introductionmentioning
confidence: 99%